Organizational learning in exporting: A bibliometric analysis and critical review of the empirical research - İpek, İlayda (International business review, 2019)
•The bibliometric analysis reveals the most influential journals, institutions, scholars, and articles in the field.•The content analysis indicates that organizational learning has stood out in the exporting research, especially in the recent decade.•Throughout time, export research on organizational learning has significantly advanced both in terms of volume and quality.•In spite of the improvements, this stream of research is still at the introduction level due to a number of weaknesses in specific areas. In the latest decades, empirical research on organizational learning in the export context has recorded an increasing trend. On the other hand, in spite of the wealth of research on the subject, no effort has yet been made to offer an integrative review to investigate the improvement of this body of knowledge. To fill this gap, this study endeavors to synthesize the stream of empirical research on organizational learning in the field of exporting published between 1997 and 2017. Initially, the relevant studies were bibliometrically analyzed on the basis of the data gathered from the Web of Science database. The bibliometric data analysis indicates the most influential publication outlets, most influential institutions, most influential scholars, and most influential articles in relation to organizational learning in the export literature. Additionally, each article was content-analyzed in terms of scope of research, research methodology, and empirical issues. The content analysis reveals that albeit significant progress, organizational learning research within the context of exporting is still at the introduction stage and certain weaknesses in scope, research designs, and conceptual understanding attract criticism.